“Reading Between the Lines”: The Bureau of Investigation, the United States Post Office, and Domestic Surveillance During World War I - Conolly-Smith, Peter (Social justice, 2009)
During World War I, the FBI (or the Bureau of Investigation, as it was then called) orchestrated the first domestic surveillance program in collaboration with the U.S. Post Office Department. Methods included wire-tapping, the use of informants, and the monitoring of mail, with the cooperation of Postmaster General Albert S. Burleson and the Post Office Department's Solicitor General, Judge William H. Lamar. Confidential memos and Post Office reports of the period show that surveillance tactics inherited, perfected, and bequeathed by J. Edgar Hoover, the director of the Bureau of Investigation, are still used in domestic spying today.